2004
DOI: 10.1002/yea.1133
|View full text |Cite
|
Sign up to set email alerts
|

Localization of proteins that are coordinately expressed with Cln2 during the cell cycle

Abstract: The localization of proteins can give important clues about their function and help sort data from large-scale proteomic screens. Forty-five proteins were tagged with the GFP variant YFP. These proteins were chosen because they are encoded by genes that display strong cell cycle-dependent expression that peaks in G 1 . Most of these proteins localize to either the nucleus or to sites of cell growth. We are able to assign new cellular component GO terms to ASF2, TOS4, RTT109, YBR070C, YKR090W, YOL007C, YOL019W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Previous studies have shown that Nbp1p is present as one or two spots at the nuclear periphery (Shimizu et al, 2000) and colocalizes with the SPB component Spc29p (Sundin et al, 2004). This localization is consistent with an association of Nbp1p either with SPBs or with kinetochores, which in yeast are clustered close to SPBs.…”
Section: Nbp1p Localizes To the Periphery And The Central Plaque Of Spbssupporting
confidence: 65%
See 1 more Smart Citation
“…Previous studies have shown that Nbp1p is present as one or two spots at the nuclear periphery (Shimizu et al, 2000) and colocalizes with the SPB component Spc29p (Sundin et al, 2004). This localization is consistent with an association of Nbp1p either with SPBs or with kinetochores, which in yeast are clustered close to SPBs.…”
Section: Nbp1p Localizes To the Periphery And The Central Plaque Of Spbssupporting
confidence: 65%
“…In addition, the protein encoded by S. cerevisiae YPR174C displays significant homology to the C-terminal half (residues 188-304) of Nbp1p (35% identical, 52% similar). Like Nbp1p, the protein encoded by YPR174C also contains a coiled-coil domain and has been localized to the SPB and nuclear periphery by fluorescence microscopy (Huh et al, 2003;Sundin et al, 2004). Both promoters of NBP1 and YPR174C contain a MluI "cell cycle box" and in both cases the mRNA expression peaks during G1 (Spellman et al, 1998;Shimizu et al, 2000), consistent with playing a role during SPB duplication.…”
Section: Nbp1-like Genesmentioning
confidence: 81%
“…The compositions of synthetic dextrose minimal medium (SD), SD-complete (SDC), and yeast peptone dextrose-rich broth medium (YPD) are described elsewhere (Sundin et al, 2004).…”
Section: Media and Strainsmentioning
confidence: 99%
“…Microcolonies were scraped off the plate and suspended in 30 l of SDC medium. A 3-4-l aliquot was mounted on a pad of 0.9% SeaKem LE agarose (FMC BioProducts, Rockland, ME) in SDC as described (Sundin et al, 2004).…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…1I). Rtt109 is nuclear and has an RNA expression pattern similar to that of Cln2 (Sundin et al 2004), but its function is not known. The mechanism through which DNA maintenance functions affect Ty1 cDNA is not completely understood but, given the common proteins and similar phenotypes, is likely to operate in the case of Ty3 as well.…”
Section: Dna Maintenance Functionsmentioning
confidence: 99%